1995
DOI: 10.1007/bf01299758
|View full text |Cite
|
Sign up to set email alerts
|

The structure of28Si above 10 MeV excitation energy III: Level scheme and shell model interpretation

Abstract: Abstract. The 2*Si level scheme up to 14.5 MeV excitation energy is reevaluated using information from two preceding papers. It consists of approximately 250 levels which are almost completely characterized according to the quantum numbers 1, re, T of the levels. The properties of positive-parity states are compared to the predictions of shell model calculations within the complete s-d basis space using the unified s-d shell Hamiltonian. A spectrum of 48 experimental T = 1 states between 9.3 and 16 MeV is repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…Extrapolating the candidate superdeformed band in 28 Si from Refs. [3,8] suggests that the bandhead should lie at around 9.3 MeV. The 9.71-MeV state is the only 0 + state in this excitation energy region (from around 8.8 MeV to 10 MeV) and is the only observed candidate for the band-head.…”
Section: Results and Spin Assignments Of Statesmentioning
confidence: 97%
“…Extrapolating the candidate superdeformed band in 28 Si from Refs. [3,8] suggests that the bandhead should lie at around 9.3 MeV. The 9.71-MeV state is the only 0 + state in this excitation energy region (from around 8.8 MeV to 10 MeV) and is the only observed candidate for the band-head.…”
Section: Results and Spin Assignments Of Statesmentioning
confidence: 97%
“…All states without an excitation-energy uncertainty have uncertainties below 1 keV as per Ref. [12]. assignment, this disagrees with the branching ratios determined from the measurement of Strandberg et al, in which no transition to the ground state from this resonance is observed [4].…”
Section: The Ex = 11142-mev Statementioning
confidence: 48%
“…The sources of resonance strengths are the direct measurements performed by Smulders and Endt [8], Lyons [9] and Strandberg et al [4]. Spectroscopic information is available from the γ-ray spectroscopy data obtained in 27 Al(p, γ) 28 Si and 24 Mg(α, γ) 28 Si reactions of Brennesien et al [10][11][12], the 28 Si(α, α ′ ) 28 Si data of Adsley et al [13], the 28 Si(p, p ′ ) 28 Si data of Adsley et al [14], and the 28 Si(e, e ′ ) 28 Si data of Schneider et al. We briefly summarise these experimental data and the information obtained from them below.…”
Section: Nuclear Datamentioning
confidence: 99%
See 2 more Smart Citations